Pariah - Rees, Dee 1976-; Young, Bradford 1977-; Dawodu, Eniola ca. 20. Jh; Oduye, Adepero 1978-; Walker, Pernell ca. 20. Jh; Davis, Aasha 1973- (<<The>> Criterion Collection, 2021)
"The path to living as one’s authentic self is paved with trials and tribulations in this revelatory, assured feature debut by Dee Rees—the all-too-rare coming-of-age tale to honestly represent the experiences of queer Black women. Grounded in the fine-grained specificity and deft characterizations of Rees’s script and built around a beautifully layered performance from Adepero Oduye, Pariah follows Brooklyn teenager Alike, who is navigating the emotional minefields of first love and heartache and the disapproval of her family as she expresses her gender and sexual identities within a system that does not make space for them. Achieving an aching intimacy with its subject through the expressive cinematography of Bradford Young, this deeply felt portrait finds strength in vulnerability and liberation in letting go." [criterion.com]
Original: USA 2011
director-approved Blu-Ray special edition features: 2K digital transfer, with 5.1 surround DTS-HD Master Audio soundtrack ; new conversation between director Dee Rees and filmmaker and professor Michelle Parkerson ; new cast reunion featuring Rees and actors Adepero Oduye, Pernell Walker, Kim Wayans, Charles Parnell, and Aasha Davis, moderated by film scholar Jacqueline Stewart ; new program on the making of the film, featuring Rees, cinematographer Bradford Young, production designer Inbal Weinberg, producer Nekisa Cooper, and editor Mako Kamitsuna, moderated by Stewart ; new interview with film scholar Kara Keeling, author of "Queer times, black futures" ; English subtitles for the deaf and hard of hearing ; plus: an essay by critic Cassie da Costa
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc